Structure, function and biosynthetic origin of octapeptin antibiotics active against extensively drug-resistant Gram-negative bacteria - Velkov, Tony (Cell Chem Biol, 2018)
Resistance to the last-resort antibiotic colistin is now widespread and new therapeutics are urgently required. We report the first in toto chemical synthesis and pre-clinical evaluation of octapeptins, a class of lipopeptides structurally related to colistin. The octapeptin biosynthetic cluster consisted of three non-ribosomal peptide synthetases (OctA, OctB, OctC) that produced an amphiphilic antibiotic, octapeptin C4, which was shown to bind to and depolarize membranes. Whilst active against MDR strains in vitro, octapeptin C4 displayed poor in vivo efficacy, most likely due to high plasma protein binding. NMR solution structures, empirical structure-activity and structure-toxicity models were used to design synthetic octapeptins active against MDR and extensively-drug resistance (XDR) bacteria. The scaffold was then subtly altered to reduce plasma protein binding, while maintaining activity against MDR and XDR bacteria. In vivo efficacy was demonstrated in a murine bacteremia model with a colistin-resistant P. aeruginosa clinical isolate.